JENIS DAN BANYAKNYA KAYU YANG DIPAKAI DALAM KONSTRUKSI JALAN REL DI HUTAN RAWA PROPINSI RIAU - Dulsalam Dulsalam; Apul Sianturi (Jurnal Penelitian Hasil Hutan, 1984)
An  observation on  the  amount  and  species of  wood  used in rail-road  construction in the swamp forests has been carried out in the PT Alam Wanasaki and PT Tenaga Kampar  concession  areas both  located  in Riau.The observation  revealed  that  the wood  species  used in rail-road construction  at the PT Alam  Wanasaki area consist of 24 species  with  a volume  of  243 m3/km. Those  used at the PT Tenaga Kampar area  consist of 12 species comprising a volume  of  204 m3/km and  the species  used at  the PT Alam  Wanasaki area are mostly  helat  (Xylopia malayana Hooh .f.) with  a total  volume  of  71 m3/km. The same  is found  at the PT Tenaga Kampar  area using a total volume  of 58 m3/km. Other wood  species  used  in  rail-road construction in both  concession  areas consist  of a number  of  commercial  species.Wood  species  which  are  considered   suitable in  the  construction  of  rail-road in  the  swamp  forests  of  PT  Alam Wanasaki are  among  others: bintangur (Callophyllum .spp.), gelam   (Eugenia spp.), medang  (Litsea spp.),   menggeris (Koompassia  spp.), pelawan  (Tristania obovata  R.Br.), punak (Tetramerista glabra Miq.),  resak (Cotylelobium melanoxylon Pierre.),  tempurung (Baccaurea spp.), and  tembesu  (Fagraea spp.),  comprising  about 16%  of the  total  volume  used in the  construction.Wood species  selected  for  rail-road construction   at  the  PT  Tenaga Kampar  concession  area are: bintangur  (Callophyllum spp.),  medang  (Litsea  spp.), and punak  (Tetramerista glabra Miq.), comprising  32% of the total amount  of wood used in the  construction.Both  companies  made  efforts  to onlv  use durable  wood  species,  however,  such  species are scarce.